Síntese de 3-Trifluoracetil-1H-pirróis N-Aril substituídos - Aquino, Estefania da Costa (2011)
This work presents a new, simple and versatile strategy for the synthesis of new N-aryl substituted 3-trifluoroacetyl-1H-pyrroles. The pyrroles were obtained by the reaction of 3-trifluoroacetyl-4,5-dihydrofuran with aryl amines of general formula ArNH2, and Ar= C6H4, 2-MeO(C6H4), 3-MeO(C6H4), 4-MeO(C6H4), 2-Me(C6H4), 3-Me(C6H4), 4-Me(C6H4), 3-F(C6H4), 4-F(C6H4), 3-Cl(C6H4), 4-Cl(C6H4), 4-OH(C6H4), 2-OH-5-Me(C6H3), 3-OH-4-Me(C6H3), 4-Br(C6H4) generating 1,1,1-trifluoro-3-(2-hydroxyethyl)-4-arylamino-3-beten-2-ones intermediates that could not be isolated. These intermediaries were submitted to Swern oxidation reaction producing 1,1,1-trifluoro-3-(2-ethanal)-4-arylamino-3-buten-2-ones that underwent intramolecular cyclization followed by aromatization by dehydratation, producing N-aryl substituted 3-trifluoracetyl-1H-pyrroles in 30-56% yield. The pyrroles obtained in this study were identified by 1H NMR, 13C NMR, and GC-Mass Espectroscopy.